Solomon [videorecording]. ([S.l] : Sony Pictures Entertainment, 2012)
After defeating his older brother, Solomon (Ben Cross) is crowned King of Israel and rules the land with love, peace and respect. Solomon meets the beautiful queen of Sheba (Vivica A. Fox), and he falls in love at first sight. When the time comes for her to return to her homeland, Solomon is unable to convince her to stay. Bereft of her beauty and companionship, he falls into a deep depression, departing from his once idyllic world of peace and luxury while his kingdom threatens to collapse.
Keywords: Bible stories, English